ACHIEVEMENTS AND DIFFICULTIES IN THE DEVELOPMENT OF mRNA VACCINES AGAINST INFECTIOUS AND CARCINOGENIC DISEASES (Journal of Medical & Health Sciences Review, 2025)
Nowadays, in the time of scientific technology, mRNA vaccines have become a promising technology stage for the revolution of vaccines. Since mRNA vaccines provide a flexible and quick method of battling infectious diseases and cancers brought on by viruses, they have significantly changed the field of vaccination. Studies have shown that mRNA vaccines can prevent COVID-19 with efficacy rates between 94% and 95%, and their potential as a potent vaccine platform is becoming more widely acknowledged. Despite being crucial in combating the pandemic of COVID-19, mRNA vaccines still have a number of drawbacks. These include their instability and disintegration, which impairs their capacity to be stored, administered, and used effectively overall. Due to its instability and negative charge, mRNA is usually encased in a procedure of transport to facilitate approaching the target cell. When mRNA is administered via lipid-nanoparticle-based vaccine delivery systems (LNPs), for example, it only enters cells to make an endosome by endocytosis without damaging the cell membrane. The pandemic of COVID-19 has accelerated the progression of platforms of mRNA vaccines, which are employed in the management and prophylaxis of several infectious ailments. The main objective of this research is to introduce several possible uses for mRNA vaccine technology, which could result in the creation of a desired vaccine design. Consequently, the general public has been able to obtain and become more familiar with a new generation of immunizations. mRNA vaccines can be used to modify the structure of an antigen in response to novel modifications in the viral genome and even to merge sequences from distinct versions. The security and defence offered by recent mRNA vaccinations are sufficient, but it will take more clinical research to ascertain how long those benefits will last.